(untitled) (Journal of the College of Basic Education, 2025)
In this paper, structural, morphological and optical of pureCdS and CdS:Co thin films with various cobalt concentrations were synthesized by the Chemicle spray pyrolysis (CSP) method. Hexagonal structure of CdS nanostructures with (020) preferred orientation is detected by XRD. According to morphological analysis, the doped films have homogeneously dispersed spherical grains with an average particle size of 42 nm. The optical parameters are estimated using transmittance and absorption spectra at 300-900 nm. Experimental results showed that when cobalt content increased, the band gap decreased as in